2017
DOI: 10.3389/fvets.2017.00093
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Link between Thermal Resistance and Virulence in Salmonella: A Review

Abstract: In some animals, the typical body temperature can be higher than humans, for example, 42°C in poultry and 40°C in rabbits which can be a potential thermal stress challenge for pathogens. Even in animals with lower body temperatures, when infection occurs, the immune system may increase body temperature to reduce the chance of survival for pathogens. However, some pathogens can still easily overcome higher body temperatures and/or rise in body temperatures through expression of stress response mechanisms. Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 191 publications
3
21
0
Order By: Relevance
“…An earlier study indicates that the absence of CRP leads to an increase in the periplasmic protease HtrA [43]. HtrA is an important protein in higher thermotolerance in E. coli [43]. In this study, we observed a significant increase in the expression of htrA (Figure 4c).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…An earlier study indicates that the absence of CRP leads to an increase in the periplasmic protease HtrA [43]. HtrA is an important protein in higher thermotolerance in E. coli [43]. In this study, we observed a significant increase in the expression of htrA (Figure 4c).…”
Section: Discussionsupporting
confidence: 71%
“…Both the alternate sigma factors rpoE and rpoH, are involved in extreme heat stress response [43]. An earlier study indicates that the absence of CRP leads to an increase in the periplasmic protease HtrA [43]. HtrA is an important protein in higher thermotolerance in E. coli [43].…”
Section: Discussionmentioning
confidence: 99%
“…The body temperature of poultry is 42 °C, hence S . Typhimurium experience constant thermal stress inside birds 46 . Therefore, the contributions of clpA and clpB genes in the in vitro survival of S .…”
Section: Resultsmentioning
confidence: 99%
“…Advanced food processing and preservation techniques are designed to reduce pathogen or toxin load or eliminate them from food; however, studies have suggested that food preservation techniques could create a sub-lethal environment ( Capozzi et al, 2009 ). It is widely accepted that the sub-lethal treatments may trigger a bacterial stress response that results in changes in gene expression, leading to not only enhanced bacterial resistance to antimicrobials or preservation conditions but also enhanced pathogen survivability and virulence ( Wesche et al, 2009 ; Spector and Kenyon, 2012 ; Verraes et al, 2013 ; Sun, 2014 ; NicAogáin and O’Byrne, 2016 ; Dawoud et al, 2017 ; Esbelin et al, 2018 ). Similarly, to overcome pathogenic microbial assault, a series of host defenses is strategically placed throughout the orogastric and intestinal tract ( Fang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%